Improvement of obstructive sleep apnea does not rescue left atrial enlargement in obese participants of a multimodal weight reduction program. Issue 12 (24th March 2023) - Sag, Sabine Julia Maria; Niebauer, Anja; Strack, Christina; Zeller, Judith; Mohr, Margareta; Sag, Can Martin; Loew, Thomas; Lahmann, Claas; Maier, Lars Siegfried; Fischer, Marcus; Baessler, Andrea; Arzt, Michael
Abstract : The aim of our study was to investigate the effect of obstructive sleep apnea (OSA) and its weight loss related improvement on left atrial (LA) area in individuals with severe obesity participating in a multimodal weight reduction (WR) program. Participants with obesity (body mass index, BMI, 40.2 ± 7.3 kg/m 2 ) underwent a 1-year WR program. Phenotyping was performed at baseline and after 12 months. Individuals were categorized according to their baseline apnea-hypopnea-index (AHI) into "no OSA" (AHI < 5) and "OSA" (AHI ≥ 5). From a total of 84 study participants, 69 completed the program. Average WR was 19.0 ± 15.7 kg after 12 months. Participants with obesity and OSA had a larger LA area at baseline as compared to participants with obesity but without OSA (22.4 ± 5.6 vs 18.8 ± 3.8 cm 2 ; P = .008). Linear regression showed significant associations of AHI and BMI with LA area. In contrast, despite a significant decrease of AHI in participants with OSA as compared to those without OSA at 1 year follow up (ΔAHI was −12 ± 14) ΔLA area did not significantly differ between groups. Multivariable linear regression showed no significant association of ΔAHI or ΔBMI with ΔLA. In conclusion, the presence of obstructive sleep apnea contributes to LA enlargement on top of obesity in our study cohort. Yet, successful WR with subsequently improved OSA was not associated with an improvement of LA area.